Short Communication: Preliminary characterization of groundcherry (Physalis angulata) from East Java Province, Indonesia based on morpho-agronomic traits - halimatus sadiyah; Andy Soegianto; Budi Waluyo; Sumeru Ashari (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sadiyah H, Soegianto A, Waluyo B, Ashari S. 2020. Short Communication: Preliminary characterization of groundcherry (Physalis angulata) from East Java Province, Indonesia based on morpho-agronomic traits. Biodiversitas 21: 759-769. Accurate knowledge of the genetic relationships between different germplasms is important for successful crop improvement programs through breeding. This work aimed to i) characterize the groundcherry germplasm collected from the field of eastern Java and Madura Island based on their morpho-agronomic performance, ii) investigate the relationships among the different germplasms, and iii) verify whether simultaneous analysis of quantitative-qualitative data (joint analysis) can reveal new clustering patterns. A total of 26 quantitative and 31 qualitative traits were measured and evaluated for 28 accessions. Principal Component Analysis (PCA) was used to select variables that had significant loading, based on a t-test, for inclusion in cluster analysis. The first clustering method was the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), which only involved quantitative variables using the Manhattan distance. This method was followed by a joint analysis using Gower dissimilarity. Nonparametric multivariate analysis of variance test showed that four clusters were the optimum number for both methods, but the clusters for each method had different members. The coefficient of variation ranged from 3.9 (fruit pH) to 45.5 (productivity per plant), indicating that improvement in the productivity in groundcherry was promising. The mean values of the morpho-agronomic traits for accessions from eastern Java and Madura Island were not significantly different, except for fruit firmness and the mean length of two internodes. In general, geographic isolation did not have much influence on the characteristics of an accession, since there were accessions from these two regions that were members of the same group, identified by the clustering analysis.